2007
DOI: 10.1021/jf071963l
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Antiplatelet Aggregatory Principles from the Leaves of Piper lolot

Abstract: The methanolic extract of Piper lolot, having shown potent inhibitory activity on platelet aggregation induced by arachidonic acid (AA) and platelet activating factor (PAF), was subjected to activity-guided isolation to yield twelve new amide alkaloids, piperlotine A-L (1-12), along with twenty-nine known compounds. Their structures were elucidated on the basis of spectroscopic analysis. The isolated compounds were tested for their inhibitory activity on the rabbit platelet aggregation. The compounds piperloti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…Pipernonaline (124) showed excellent larvicidal activity against Aedes aegypti, comparable to pirimiphos-methyl, the insecticide commonly used; 201 retrofractamide A (126) offered satisfactory adipogenic activity, can be considered a promising candidate for the development of antidiabetic agents, 28 and the N-[trans-cinnamoyl] pyrrolidine (36) inhibitor of platelet aggregation with IC 50 of 7.3 mg/mL, comparable with aspirin (IC 50 5.5 mg/mL), an anti-clotting agent used clinically to combat the formation of thrombi. 131 Data demonstrated the biological and medicinal importance of piplartine isolated from the roots of P. chaba, and indicated that E-piplartine may be a promising candidate for use in combinatorial treatments to combat cancer. 275 To date, the presence of 277 amides from Piper has been reported while data from chemical shifts in 13 C NMR is available for 182 compounds.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 97%
“…Pipernonaline (124) showed excellent larvicidal activity against Aedes aegypti, comparable to pirimiphos-methyl, the insecticide commonly used; 201 retrofractamide A (126) offered satisfactory adipogenic activity, can be considered a promising candidate for the development of antidiabetic agents, 28 and the N-[trans-cinnamoyl] pyrrolidine (36) inhibitor of platelet aggregation with IC 50 of 7.3 mg/mL, comparable with aspirin (IC 50 5.5 mg/mL), an anti-clotting agent used clinically to combat the formation of thrombi. 131 Data demonstrated the biological and medicinal importance of piplartine isolated from the roots of P. chaba, and indicated that E-piplartine may be a promising candidate for use in combinatorial treatments to combat cancer. 275 To date, the presence of 277 amides from Piper has been reported while data from chemical shifts in 13 C NMR is available for 182 compounds.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 97%
“…Mục đích của bài báo này tập trung nghiên cứu ảnh hưởng của một số dịch chiết thực vật của Việt Nam, có hoạt tính sinh học, đã được dùng đề chữa bệnh trong dân gian (Abdullah et al, 2014;Abrahim et al, 2012;Behera et al, 2013;Dosoky et al, 2015;Li et al, 2007;Mahabusarakam et al, 2005;Saraiva et al, 2012;Padmapriya & Poonguzhali, 2015;Wu et al, 2015;Đỗ Tất Lợi, 1991). Tuy nhiên, những dịch chiết này chưa được nghiên cứu đầy đủ về hoạt tính gây độc tính tế bào và khả năng loại bỏ gốc tự do in vitro trên tế bào HaCaT để trả lời cho một số câu hỏi như: Các dịch chiết thực vật này có tác dụng gây độc tế bào keratinocyte HaCaT hay không và có hay không sự khác nhau về độc tính giữa dịch chiết methanol và hexane?…”
Section: Mở đầUunclassified
“…Sarmentine, 1-(1-pyrrolidinyl)-(2 E ,4 E )-2,4-decadien-1-one, is a Piper amide with several biological properties, including antiplasmodial, antimycobacterial, and antituberculosis activity (Rukachaisirikul et al, 2004 ; Tuntiwachwuttikul et al, 2006 ), as well as antiplatelet aggregation (Li et al, 2007 ). Interest in sarmentine as a biopesticide renewed when its herbicidal activity was discovered through a bioactivity-guided isolation of the active components of the fruits of Piper sarmentosum and Piper nigrum (Huang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%